Chiral Switch Drugs for Asthma and Allergies: True Benefit or Marketing Hype - Blake, Kathryn (Mary Ann Liebert, Inc., 2013)
Enantiomers are one of several possible molecular configurations present in a drug that has at least 1 chiral center. A drug containing 2 or more enatiomers is called a racemic mixture. Enatiomers are being developed from racemic mixtures as drugs in their own right often to extend patent protection of highly popular drugs. However, the therapeutic advantages of single enantiomer drugs developed for respiratory use such as levalbuterol, arformoterol, and levocetirizine over their racemate has been disappointing. In addition, single enantiomer drugs may be several fold more expensive than the racemic drug. New single enantiomer drugs, which are stable (no interconversion back to the racemate) and have fewer adverse effects and a more predictable pharmacodynamic or pharmacokinetic profile would confer a therapeutic advantage and thus would be beneficial for clinical use.